Novel Application of 210Po-210Pb Disequilibria to Date Snow, Melt Pond, Ice Core, and Ice-Rafted Sediments in the Arctic Ocean - Baskaran, Mark; Krupp, Katherine (Frontiers in Marine Science, 2021)
We collected surface ocean water, snow, grab ice, ice core, melt pond and ice-rafted sediment (IRS) from 5 ice stations during the Western Arctic US GEOTRACES cruise (USGCG Healy; August 10 – October 7, 2015) and analyzed for 210Po (T1/2 = 138.4 days) and 210Pb (T1/2 = 22.3 years) in dissolved and particulate phases (snow, grab ice, ice core, surface seawater) to investigate the 210Po:210Pb disequilibria in these matrices. Thirteen aerosol samples, using a large-volume aerosol sampler (PM10), from Dutch Harbor, AK to North Pole, were also collected and analyzed for 210Po/210Pb to quantify the atmospheric depositional input to the snow and surface waters. Falling snowfall is tagged with 210Po/210Pb ratio (AR) similar to that in the air column from the cloud condensation height to air-sea interface. From the measured AR in aerosol and snow, modeling the sources of 210Po and 210Pb input to the melt pond, and measured disequilibrium in ice core and ice-rafted sediment, we show 210Po/210Pb AR is a novel chronometer to date snow, ice core, melt pond, and IRS. The calculated mean ages of aerosol, snow, melt pond and IRS are 12 ± 7 (n = 13), 13 ± 11 (n = 6), 60 ± 14 (n = 4), and 87 ± 23 (n = 6) days, respectively. The average IRS age corresponds to an average drift velocity of sediment-laden ice of 0.18 ± 0.06 (n = 6) m s–1. We report highly elevated levels of 210Po and 210Pb in snow and melt pond compared to those in Arctic surface seawater and enrichment of 210Po compared to 210Pb onto particles extracted from snow, ice and melt ponds. The observed disequilibrium between 210Po and 210Pb in ice could serve as a quantitative tool in delineating multiple-year ice from seasonal ice as well as a metric in quantifying the speed of ice/snow melting and delay in autumn freeze.